2022
DOI: 10.1002/jia2.26044
|View full text |Cite
|
Sign up to set email alerts
|

Adherence challenges with daily oral pre‐exposure prophylaxis during pregnancy and the postpartum period in South African women: a cohort study

Abstract: Introduction Daily oral pre‐exposure prophylaxis (PrEP) can reduce HIV acquisition. However, prevention effectiveness requires daily adherence prior to and during periods of sexual activity. Little is known about pharmacologic measures of PrEP adherence during pregnancy and postpartum and the factors related to optimal adherence during periods of sexual activity in this population. Methods Between August 2019 and October 2021, we enrolled pregnant women without HIV at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…Our findings support that knowledge of partners’ HIV status is important for PrEP use and that women with partners known to be living with HIV are highly motivated to use daily oral PrEP, similar to studies among pregnant PrEP users in South Africa [38]. Dispensing HIV self-tests to pregnant women attending antenatal care to give to their male partners is scaling up in East and Southern Africa to increase testing coverage among men [27,39–42].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings support that knowledge of partners’ HIV status is important for PrEP use and that women with partners known to be living with HIV are highly motivated to use daily oral PrEP, similar to studies among pregnant PrEP users in South Africa [38]. Dispensing HIV self-tests to pregnant women attending antenatal care to give to their male partners is scaling up in East and Southern Africa to increase testing coverage among men [27,39–42].…”
Section: Discussionsupporting
confidence: 83%
“…To date, few PrEP studies among pregnant and postpartum women have incorporated objective markers of PrEP adherence. A recent study that followed South African women who initiated PrEP in pregnancy until 12 months postpartum found that 72% of all DBS samples had TFV-DP concentrations corresponding with <2 doses/week [45] and frequency of any quantifiable TFV-DP was higher in pregnancy than postpartum [38]. We similarly found high frequency of TFV-DP concentrations corresponding with <2 doses/week (64% overall) and lower adherence levels postpartum than pregnancy.…”
Section: Discussionsupporting
confidence: 63%
“…Only 2% met the threshold consistent with approximately 7 doses/week. 12 Although different assays and adherence algorithms were used, our estimate for 2-5 doses/week (score of 3 or 4) was similar at 33%. However, we observed a higher proportion with drug levels consistent with daily dosing (score of 5; 10%).…”
Section: Discussionmentioning
confidence: 78%
“…7,8 Although data are still limited, the available studies suggest that pharmacologically confirmed adherence may also be low in this population. 12 This gap may be particularly important for pregnant and breastfeeding women. Pharmacokinetic/pharmacodynamic modeling suggests that longer lead times may be needed to reach protective tenofovir concentrations in the lower female genital tract.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, oral tenofovir disoproxil fumarate (TDF) 300 mg in combination with emtricitabine (FTC) 200 mg (Truvada®) is approved for prevention of HIV-1 acquisition in men and women in the United States and several other countries worldwide ( Grant et al., 2010 ; Baeten et al., 2012 ; Thigpen et al., 2012 ). The daily dosing requirement and systemic side effects, primarily gastrointestinal (GI), among other barriers including stigma and lack of support from family or partner, have made it difficult, particularly for AGYWs, to adhere to daily oral TDF/FTC for HIV-1 prevention ( Van Damme et al., 2012 ; Magazi et al., 2014 ; van der Straten et al., 2014b ; Corneli et al., 2015 ; Marrazzo et al., 2015 ; Corneli et al., 2016 ; Amico et al., 2017 ; Joseph Davey et al., 2022 ; Tapsoba et al., 2022 ). Oral tenofovir alafenamide (TAF) combined with FTC (Descovy®), which shows fewer side effects, was recently approved by the United States Food and Drug Administration for HIV-1 prevention, but only among individuals whose primary risk of HIV-1 acquisition is not through vaginal exposure ( Mayer et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%